Color Thresholding Techniques Performance for Night Vision Surveillance Using Thermal Imaging - Noor Amira Syuhada Mahamad Salleh; Kamarul Hawari Ghazali; Fatin Izzwani Azman (Proceeding of the Electrical Engineering Computer Science and Informatics, 2014)
Visible surveillance is commonly an active research worldwide. The need of surveillance allows thermal imaging to participate in this study activity. The drawback of visible surveillance for night monitoring is overcome by the technology of the thermal imaging. To achieve the goal of the surveillance system , the works on detection must be very efficient to do the detection Throughout this research , we developed an algorithm involving thresholding technique for subject detection using thermal image to find the for night surveillance system.